Perancangan Sistem Informasi Pembelian, Penjualan dan Persediaan di UD. Koleksi Monza - Hita Hita; Joosten Joosten (LPPM Universitas Bina Sarana Informatika, 2023)
The information system is also one of the most important parts for companies in increasing productivity, both in obtaining information, processing, and using the information, especially for the benefit of the company. UD. Monza Collection is a form of business that is engaged in distributors for women's clothing such as shorts, leggings, tank tops, and others and then sells them wholesale. The problem with the store is that the store often has difficulty in knowing the amount of raw materials by the distribution staff quickly and the calculation of the number of finished goods by the warehouse staff who are very prone to errors, this will result in delays in distribution and sales activities. The system design methodology used is the System Development Life Cycle (SDLC) methodology. The design of the input system using Microsoft Visual Studio 2015, The design of the system output using Crystal Report and data storage using Microsoft SQL Server 2014. The result of this writing is a desktop design that makes it easy to find out the available stock and makes it easy to make the required reports quickly. So that the results of this information system design can help the store in managing information and computerized business processes.